The people there in - Lee, Mildred (New York Houghton Mifflin/Clarion Books, 1980)
Love blossoms and grows between a crippled girl and a troubled botanist who has abandoned turn-of-the-century Boston for a life in the southern Appalachians.
Keywords: Mountain life -- Fiction; Botany -- Fiction; Appalachian Mountains -- Fiction